2009
DOI: 10.1111/j.1939-3938.2009.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities in the forensic sexual assault examination related to skin color

Abstract: Little is known about the role of skin color in the forensic sexual assault examination. The purpose of this study was to determine whether anogenital injury prevalence and frequency vary by skin color in women after consensual sexual intercourse. The sample consisted of 120 healthy (63 Black, 57 White) women who underwent a forensic sexual assault examination following consensual sexual intercourse. Experienced sexual assault forensic examiners using visual inspection, colposcopy technique with digital imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…Investigators describe differences in injury patterns, types, severity, and number between people of different races and/or ethnicities with respect to sexual assault, childbirth-related injury, pressure ulcer formation, and healing (Baumgarten et al, 2004; Fogerty et al, 2008; Saladin & Krause, 2009; Sommers, 2007; Sommers et al, 2008). For example, in a population of women studied after consensual sexual intercourse, Sommers et al found that not only was injury prevalence significantly higher in White as compared with Black/African American women, but the effect of race/ethnicity became nonsignificant after adding skin color values to the model predicting occurrence of genital injury (Sommers et al, 2008, 2009). These findings indicated the spurious nature of the relationship between race/ethnicity and injury prevalence and demonstrated that skin color rather than race/ethnicity is likely the important variable in injury prevalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators describe differences in injury patterns, types, severity, and number between people of different races and/or ethnicities with respect to sexual assault, childbirth-related injury, pressure ulcer formation, and healing (Baumgarten et al, 2004; Fogerty et al, 2008; Saladin & Krause, 2009; Sommers, 2007; Sommers et al, 2008). For example, in a population of women studied after consensual sexual intercourse, Sommers et al found that not only was injury prevalence significantly higher in White as compared with Black/African American women, but the effect of race/ethnicity became nonsignificant after adding skin color values to the model predicting occurrence of genital injury (Sommers et al, 2008, 2009). These findings indicated the spurious nature of the relationship between race/ethnicity and injury prevalence and demonstrated that skin color rather than race/ethnicity is likely the important variable in injury prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians and researchers have published findings relating the importance of skin color in health care. These include differences in the potential for injury when faced with forces associated with trauma (soft tissue injury), friction/shearing (pressure ulcers), and stretching (childbirth; Howard, Davies, DeLancey, & Small, 2000; Robinson, Norwitz, Cohen, McElrath, & Lieberman, 1999; Saladin & Krause, 2009; Sommers et al, 2009). Accurate evaluation of skin color is important in both clinical and research settings (Bennett, 1995; Berardesca, Derigal, Leveque, & Maibach, 1991; Ha et al, 2009; Lindholm et al, 2008).…”
mentioning
confidence: 99%
“…Even with higher reports of sexual assault, African American women are less likely to report being sexually assaulted and received less support than White women (Tillman et al, 2010).…”
Section: Differences Based On Ethnicity and Racementioning
confidence: 93%
“…Many of the differences have been attributed to cultural norms, help-seeking behaviors, and availability of accessible services (Cuevas & Sabina, 2010;Tillman, Bryant-Davis, Smith, & Marks, 2010). Ethnic minority victims report more undesired social reactions from others than do White victims (Ullman & Filipas, 2001).…”
Section: Differences Based On Ethnicity and Racementioning
confidence: 99%
“…Petechiae may also be present on the skin on the victim's neck, head, face, forehead, around eyes and ears, conjunctivae, and buccal mucosa (Clarot et al, 2005;Dix & Calaluce, 1998;. Physical findings on the skin may be more difficult to identify in patients with darker skin; one study found that it was more difficult to find anogenital injuries in patients with darker skin than in those with lighter skin when they were examined after consensual intercourse (Sommers et al, 2009). This is an area for further research as far as its application to strangulation injuries.…”
Section: Skinmentioning
confidence: 99%